Nursing postgraduates learning experience of professional curriculum in China: A qualitative study - Hongmei Jiang; Ting Zhang; Suofei Zhang; Huijuan Ma; Yu Luo (Wiley, 2024)
Abstract Aim This study adopted the qualitative research method, aiming to explore the learning experience of nursing graduate professional curricula in China from the perspective of students and provided a basis for the continuous improvement of nursing graduate training. Design A qualitative study. Methods A purposive sampling method was employed to conduct semi‐structured in‐depth interviews with 14 nursing master's students enrolled in professional curricula from September 03, 2021, to December 8, 2022. The Colaizzi seven‐step analysis method was utilized for data analysis, summarization and extraction. Results Four themes emerged from the study findings: (i) The study of professional curricula is the cornerstone of scientific research work, but it is relatively boring; (ii) The teaching methods and assessment methods of postgraduate education need to be diversified; (iii) The postgraduate education needs to increase the study time of specialized courses and highlight the specialty characteristics; (iv) the study of professional curricula can enhance the comprehensive ability of postgraduate students. Conclusion The study of professional curricula for post‐graduate nursing students plays an important role in the development of post‐graduate research and can statistically significant improve their comprehensive ability, but there are some problems such as boring courses, single teaching assessment methods and insufficient time. In the future teaching reform, it is necessary to highlight the specialty characteristics of nursing scientific research, optimize curriculum education and improve students' scientific research knowledge and thinking. Patient and Public Contributions We thank all participants for their valuable input throughout the study.